AGE AND GROWTH OF THE MARINE CATFISH TACHYSURUS THALASSINUS (RUPPELL) FROM MANDAPAM WATERS - Menon, N Gopinatha (Indian Journal of Fisheries, 2011)
Catfishes of the family Tachysuridae form an important demersal fisheryresource at M'lndapani. The irawl fishery here consists of four commerciallyimportant species, they being, in the decreasing order of abundance, Tachysurusthalassinus, T. dussumieri, T. caelatus and T. platystomus.